The contribution of the quality of photos uploaded on social media to tourists' decision to visit Labuan Bajo - Kusherdyana Kusherdyana; Soendjana Suganda; Hery Soesanto; Singgih Tri Wibowo; Darmawan Sundayana (Universitas Merdeka Malang, 2022)
Photos uploaded by tourists who have visited a destination will attract someone's interest to visit that destination. Therefore, this study is expected to reveal how much influence the quality of photo uploads on social media has on the decision to visit tourists. The research approach used in this research is descriptive verification. The population in this study are tourists who visit Labuan Bajo, NTT Province. Through the purposive sampling technique obtained 72 respondents. This study found that photos uploaded by tourists who have visited Labuan Bajo greatly influence the decision to visit tourists, especially millennial tourists because they are considered more authentic in providing an overview of the condition of a destination compared to content originating from official institutions.